2020
DOI: 10.2147/ott.s240022
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA ASB16-AS1 Functions as a miR-760 Sponge to Facilitate the Malignant Phenotype of Osteosarcoma by Increasing HDGF Expression</p>

Abstract: Purpose: ASB16 antisense RNA 1 (ASB16-AS1) is a cancer-associated long non-coding RNA that contributes to tumorigenesis and tumor development. Nevertheless, to the best of our knowledge, whether and how ASB16-AS1 is implicated in osteosarcoma (OS) malignancy remains unclear and therefore warrants exploration. Our current study focused on making in-depth investigation of ASB16-AS1 in OS. In the present study, the expression pattern of ASB16-AS1 in OS tissues and cell lines was analyzed. In addition, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The fact that HDGF is a representative member of a gene family ( Figure 1; Figure 2) might be advantageous when we consider it as a therapeutic target. Recently, the significant roles of HDGF in malignant diseases were reported for many non-digestive malignant diseases, including osteosarcoma [61,62], endometrial cancer [63,64], lung cancer [65][66][67], malignant glioma [68][69][70], cervical cancer [71], ovarian cancer [72] and breast cancer [73]. Thus, HDGF is considered as a potential target molecule for anticancer therapy.…”
Section: Hdgf As a Potential Target Molecule For Anticancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that HDGF is a representative member of a gene family ( Figure 1; Figure 2) might be advantageous when we consider it as a therapeutic target. Recently, the significant roles of HDGF in malignant diseases were reported for many non-digestive malignant diseases, including osteosarcoma [61,62], endometrial cancer [63,64], lung cancer [65][66][67], malignant glioma [68][69][70], cervical cancer [71], ovarian cancer [72] and breast cancer [73]. Thus, HDGF is considered as a potential target molecule for anticancer therapy.…”
Section: Hdgf As a Potential Target Molecule For Anticancer Therapymentioning
confidence: 99%
“…Recently, non-coding RNAs, such as microRNAs and long non-coding RNAs (lncRNAs), which modulate the function of the target genes, have been shown to have an important role in several diseases [77,78]. Indeed, various microRNAs [40,61,62,[64][65][66][67]69,72] and lncRNAs [49,61,69,71,73] have been suggested to be involved in the regulation of the functions of HDGF, findings that may support the development of HDGF-targeting therapies. For instance, lncRNA HLA complex P5 (lnc HCP5) was reported to cause gemcitabine resistance in pancreatic cancer cells, through the upregulation of miR-214-3p and its target gene, HDGF [40].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The inhibition of proliferation, migration, and invasion, along with increased apoptosis in osteosarcoma cells, was associated with impaired tumor growth in vivo . 27 Taken above, we proposed that overexpression of miR-140 impaired tumor growth of osteosarcoma by suppressing osteosarcoma cell migration, invasion, and promoting apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have found that ASB16-AS1 promotes cell proliferation in glioma, hepatocellular carcinoma, cervical cancer, non-small cell lung cancer and in osteosarcoma [17][18][19][20][21] . However, the biological function and molecular mechanism of ASB16-AS1 in adrenocortical carcinoma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that E3 ligase β-TrCP1 (BTRC) target HuR for ubiquitin-mediated protein degradation 14,16 . Several studies have found that ASB16-AS1 regulate proliferation in glioma, hepatocellular carcinoma, cervical cancer, non-small cell lung cancer, and in osteosarcoma [17][18][19][20][21] . However, whether ASB16-AS1 plays an important role in adrenocortical carcinoma remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%